Хозяйственная продуктивность дигаплоидов и удвоенных гаплоидов у сахарной свеклы (Beta vulgaris L.) - Юданова, С.С.; Мелентьева, С.А.; Малецкая, Е.И.; Татур, И.С.; Малецкий, С.И. (Фактори експериментальної еволюції організмів, 2013)
A goal of the presented paper was the crop productivity estimation of dihaploid and double haploid plants after apozygotic (uniparental) reproduction of heterosis hybrid. Methods. 8 dihaploid apozygotic progenies of heterosis hybrid Lenturon and 11 double haploid progenies were investigated. In the investigated material were evaluated (i) crop productivity (t/ha), (ii) sugar content in root (%), (iii) sugar yield. Results. Dihaploid progenies don’t register a reduction of crop productivity. Some of progenies even exceed a result of the initial hybrid. Double haploids register also a high level of crop productivity, but this material show greater variability. Conclusions.This result shows a possibility using of apozygotic progenies for breeding purposes. A use of uniparental (apozygotic) reproduction makes it possible to enlarge the genetic diversity of breeding materials.